Mosaico de forros: formas de ascensão econômica e social entre os alforriados(Mariana, 1727-1838) - Rogeria Cristina Alves (2011)
This work aims at investigating the ways of economical and social rising experienced by theones who had obtained emancipation through the Termo de Mariana, between 1727 and 1838.Based on the wills and post-mortem documents which belonged to the emancipated men andwomen, it is analyzed here the possibilities both found and created by them to sustainthemselves, to get material assets, and to obtain social recognition in the society to which theybelonged. It is important to consider the ways of economical and social rising available to theemancipated ones: the wealth available to them and the social rising in that society almostexclusively constituted of free and white people. These are the factors that contribute to showthe malleability of the colonial society of Minas Gerais, highlighting the nuance of everydayrelationships based on European models, but, which, in practice, could admit other references,a process that certainly characterizes this society. Hence, the emancipated people created thestrategies which were possible for them, and were protagonists of different life stories. These,when examined carefully, reveal a distance from a pattern and the resemblance to a mosaic,which gathered different emancipated individuals with a common purpose: ascendeconomically and socially in the Minas Gerais at that moment.